2015
DOI: 10.1016/j.atmosres.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different profiles to characterize the atmosphere for three MODIS TIR bands

Abstract: 8Accurate Land surface temperature (LST) retrievals from sensors aboard orbiting 9 satellites are dependent on the corresponding atmospheric correction, especially in the 10 Thermal InfraRed (TIR) spectral domain (8-14 µm). To remove the atmospheric effects from at-11 sensor measured radiance in the TIR range it is needed to characterize the atmosphere by 12 means of three specific variables; the upwelling path and the hemispherical downwelling 13 radiances plus the atmospheric transmissivity. Those variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…The accuracy of NCEP/FNL in Europe was similar to the research of Pérez-Planells et al [18] in Spain. According to the validation of MODIS TIR bands by Pérez-Planells et al [18] ⁄ for atmospheric downward radiance.…”
Section: Comparison With Previous Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…The accuracy of NCEP/FNL in Europe was similar to the research of Pérez-Planells et al [18] in Spain. According to the validation of MODIS TIR bands by Pérez-Planells et al [18] ⁄ for atmospheric downward radiance.…”
Section: Comparison With Previous Studiessupporting
confidence: 68%
“…Moreover, ERA-Interim is recommended for use with the atmospheric correction of thermal infrared data in high water vapor content conditions. The accuracy of NCEP/FNL in Europe was similar to the research of Pérez-Planells et al [18] in Spain. According to the validation of MODIS TIR bands by Pérez-Planells et al [18] using global radiosonde profiles, the biases (RMSEs) of atmospheric transmittances for NCEP/FNL were between −0.019 (±0.02) and 0.007 (±0.04).…”
Section: Comparison With Previous Studiessupporting
confidence: 68%
See 1 more Smart Citation
“…This simulated profile is interpolated spatially and temporally to the selected site and it is representative of the atmosphere in a 1 • spatial resolution. This atmospheric profile was demonstrated to be the best option to correct the atmospheric effect compared with other profiles like that offered by the MOD07 product [34].…”
Section: Landsat 7 Etm+ Land-surface Temperaturesmentioning
confidence: 99%
“…These differences could be due to the empirical expression to retrieve the minimum emissivity from MMD at the AST05 product algorithm, which is not fitted to low contrast surfaces [12], as well as to the atmospheric correction applied at the product AST05, since NCEP atmospheric profiles are less accurate than profiles obtained by in situ radiosoundings [44,45]. As an example, Pérez-Planells et al in [45] showed that using interpolated NCEP profiles instead of radiosoundings yielded errors of ±0.6 K for sites close to sea level, which would be equivalent to ±0.01 in terms of emissivity. Moreover, previous studies pointed out that ASTER product atmospheric correction loses accuracy in warm and humid areas close to sea level [23,24].…”
Section: Lse and Lst Evaluationmentioning
confidence: 99%